2000
DOI: 10.1177/026835550001500103
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Varicose Long Saphenous Veins with Sclerosant in Microfoam Form: Long-Term Outcomes

Abstract: Objective: To determine whether the injection of sclerosant in microfoam form offers a clear alternative to surgery in large varices of the lower extremities. Design: Retrospective observational follow-up study (3–6 years). Patients: Five hundred lower limbs in which pretreatment duplex ultrasound demonstrated insufficiency of sapheno-femoral junctions (diameters 9–32 mm) and long saphenous veins. Main outcome measure: Obliteration and subsequent disappearance of treated veins. Results: After ≥ 3 years follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 6 publications
2
60
1
10
Order By: Relevance
“…There are many works providing good results about the use of POL foam sclerotherapy (Alos et al, 2006;Cabrera et al, 2000;Cavezzi and Frullini, 1999;Frullini, 2000;Gachet, 2001;Garcia-Mingo, 1999;Hsu and Weiss, 2003;Ouvry et al, 2008;Rabe et al, 2008;Redondo and Cabrera, 2005;Santos, 2008;Tessari, 2000). The ability to be agitated and foamed increases the potency of detergents from 2 to 4 times by mechanically displacing blood and thus maximizing surface area and time in contact with endothelium.…”
Section: Foaming Processmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many works providing good results about the use of POL foam sclerotherapy (Alos et al, 2006;Cabrera et al, 2000;Cavezzi and Frullini, 1999;Frullini, 2000;Gachet, 2001;Garcia-Mingo, 1999;Hsu and Weiss, 2003;Ouvry et al, 2008;Rabe et al, 2008;Redondo and Cabrera, 2005;Santos, 2008;Tessari, 2000). The ability to be agitated and foamed increases the potency of detergents from 2 to 4 times by mechanically displacing blood and thus maximizing surface area and time in contact with endothelium.…”
Section: Foaming Processmentioning
confidence: 99%
“…PEM is a pharmaceutical form of micro-foam that emulates the foam originally produced and studied by Cabrera (Cabrera et al, 2000(Cabrera et al, , 2003(Cabrera et al, , 2004 in a standardized way. It is generated and dispensed using a pressurized canister mechanism depicted in Fig.…”
Section: Foaming Processmentioning
confidence: 99%
“…In another study done by Cabrera et al [38], 81% of the treated GSV with foam therapy remained occluded after 3 years or more. Also, Thomasset et al [39] reported that, with 3 months as a median time of follow up 79% of cases showed complete occlusion of desired veins, 14% showed partial occlusion and the rest 6% showed complete patency.…”
Section: Discussionmentioning
confidence: 88%
“…Existen técnicas menos invasivas que reducen estas complicaciones, entre ellas, la inyección ecoguiada de espuma esclerosante 2,3 , la ablación de las venas safenas con endoláser 4 o mediante la radiofrecuencia 5,6 y últimamente obliteración de la vena safena con cianoacrilato 7 . La ablación de los troncos safenos con el uso de radiofrecuencia consiste en la introducción de una sonda endoluminal que permite aplicar energía tér-mica controlada sobre la superficie interna de la pared venosa, injuria térmica que produce inicialmente una destrucción de la capa íntima y trombosis de la vena, y posterior engrosamiento y contracción de las fibras de colágeno de la capa media y adventicia, con reducción drástica del lumen e inflamación perivenosa, y finalmente, la obliteración definitiva de la vena, impidiendo de este modo el reflujo venoso patológico y la hipertensión venosa secundaria 8,9 .…”
Section: Introductionunclassified